1997
DOI: 10.1007/s000330050035
|View full text |Cite
|
Sign up to set email alerts
|

New solutions for laminar boundary layers with cross flow

Abstract: In some three-dimensional laminar boundary layer problems a coordinate decomposition reduces the governing equations to a primary nonlinear ordinary differential equation describing the streamwise flow in a semi-infinite domain and a secondary linear equation coupled to the primary solution describing the cross flow of infinite spanwise extent. Five new cross-flow problems of this type are investigated within the confines of laminar boundary layer theory. First, the equation for uniform flow transverse to a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…͓URL 10. ͑Color online͒ Snapshots of the vertical velocity w of a synchronous axisymmetric state in ͑a͒ a meridional section and ͑b͒ a horizontal section at z = 0.05␥ at a mean Re= 6 ϫ 10 4 modulated by 5% at frequency f = 1.0, together with ͑c͒ a space-time plot of w at z = 0.05␥ with r ͓0,1͔ ͑vertical axis, with r increasing from top to bottom͒ and t ͓0,10͔ ͑horizontal axis, with t increasing from left to right͒ ͑enhanced online͒.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…͓URL 10. ͑Color online͒ Snapshots of the vertical velocity w of a synchronous axisymmetric state in ͑a͒ a meridional section and ͑b͒ a horizontal section at z = 0.05␥ at a mean Re= 6 ϫ 10 4 modulated by 5% at frequency f = 1.0, together with ͑c͒ a space-time plot of w at z = 0.05␥ with r ͓0,1͔ ͑vertical axis, with r increasing from top to bottom͒ and t ͓0,10͔ ͑horizontal axis, with t increasing from left to right͒ ͑enhanced online͒.…”
Section: Discussionmentioning
confidence: 99%
“…Both the von Kárman and the Bödewadt crossflows have the feature that they satisfy no slip at a wall and asymptotically tend to zero far above the wall, but there exist other crossflows that do not exhibit this feature. 10 The controversy with the Bödewadt similarity solution is that it requires radial inflow from infinity to approach similarity in the boundary layer as r → 0. 11 The speculation has been that this boundary layer flow may "break down" at some finite radius and hence Bödewadt's similarity solution may not be achieved in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Altaç et al [5] studied the mixed convection flow subjected to upward cross flow. Many other significant cross-flow studies can be obtained in these reported research papers [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 85%
“…Thus it also arises in a three-dimensional boundary layer flow analysis, as reported by Weidman [6]. In that situation the problem is to determine, for a given streamwise uniform shear flow of strain rate β, possible fully-developed cross flows that may exist.…”
Section: Constant Wall Temperaturementioning
confidence: 99%
“…belong to the classical topics of fluid mechanics. Due to their wide breath of technical and environmental applications [2][3][4] the general research interest in shear driven flows [5][6][7][8] and their heat transfer characteristics [9,10] still remains a viable area of research.…”
Section: Introductionmentioning
confidence: 99%